Implementasi Metode Weighted Product Pada Sistem Pendukung Keputusan Pemilihan Lembaga Bimbingan Belajar - Muhammad Irfan; Yanuardi; Nunik Yudaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Tutoring provides a process of learning assistance to children to overcome learning difficulties. Currently, there are many tutoring or tutoring institutions that have special programs for preparation for entering state universities. Along with the emergence of Bimbel, it makes parents or students experience difficulties in making choices. To choose the right Bimbel institution, you need to know one by one the profile and services provided by that institution. This will take a long time to make a choice. This study aims to build a Decision Support System (SPK) using the Weighted Product (WP) method to determine tutoring institutions so that parents or prospective students can make the right choices and according to their needs. The WP method can obtain the best alternative based on multiplication between attributes and each attribute is first raised to the power of its weight. Based on the case studies conducted, the highest preference score was obtained for Ganesha Operation (A2) with a value of 0.259, followed by Latis Supercamp (A4) with a value of 0.251, Nurul Fikri (A3) with a value of 0.247 and Brain Academy with a value of 0.244. The results of the DSS which are built with the results of manual calculations get the same value. Besides that, in testing using Black-Box Testing, all functionality can run as it should.